KEMAMPUAN GURU SEKOLAH DASAR DALAM MENERAPKAN PEMBELAJARAN TEMATIK DI SEKOLAH - Munasik, Munasik (Jurnal Pendidikan, 2014)
Integrated thematic learning is learning that uses the theme to associate some subjects that can provide meaningful experiences and provide benefits for students. This study aims to determine the perception of lower grade elementary school teachers towards the implementation of thematic learning in learning; constraints faced by teachers in developing lesson plans, selecting media, and choose appropriate learning methods that can improve student learning outcomes. This study used a qualitative approach. Data collection techniques such as questionnaires, observation, interviews, documentation, which is used to study the problems in the thematic learning in low-grade elementary school. These results indicate that teachers' understanding and knowledge of thematic learning is good enough. Integrated learning is an instructional model that is most suitable for low-grade primary school students, because the thematic learning / integrated, the child may be invited to participate actively in exploring the topics or events. The difficulty is in the preparation and implementation of the lesson plan is still encountering many obstacles, especially in the search for methods and media to suit all themes, while determining the success of the measuring instrument thematic learning (learning evaluation) that can accommodate some of the materials that are combined rather difficult to formulate. The way out is taken of teachers in the face of difficulties develop thematic learning circumvented by increasing discussions with colleagues and multiply by searching reference sources on the internet or other web. Pembelajaran tematik adalah pembelajaran terpadu yang menggunakan tema untuk mengaitkan beberapa mata pelajaran sehingga dapat memberikan pengalaman yang bermakna serta memberikan keuntungan bagi siswa. Penelitian ini bertujuan untuk mengetahui persepsi guru SD kelas rendah terhadap penerapan pembelajaran tematik dalam pembelajaran; kendala yang dihadapi guru dalam mengembangkan RPP, memilih media, dan memilih metode pembelajaran yang tepat sehingga dapat meningkatkan hasil belajar siswa. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data berupa kuisioner, observasi, wawancara, dokumentasi, yang digunakan untuk mengkaji permasalahan dalam pembelajaran tematik di kelas rendah SD. Hasil penelitian ini menunjukan bahwa pemahaman dan pengetahuan guru tentang pembelajaran tematik sudah cukup baik. Pembelajaran terpadu merupakan suatu model pembelajaran yang paling sesuai untuk siswa SD kelas rendah, karena dalam pembelajaran tematik/terpadu, anak dapat diajak berpartisipasi aktif dalam mengeksplorasi topik atau kejadian. Kesulitannya adalah dalam penyusunan dan pengimplementasian rencana pelaksanaan pembelajaran masih menemui kendala terutama dalam mencari metode dan media yang sesuai dengan semua tema, sementara penentuan alat ukur keberhasilan pembelajaran tematik (evaluasi pembelajaran) yang bisa mengakomodir beberapa materi yang digabungkan agak sulit untuk dirumuskan. Jalan keluar yang diambil guru dalam menghadapi berbagai kesulitan mengembangkan pembelajaran tematik disiasati dengan memperbanyak diskusi dengan teman sejawat dan memperbanyak referensi dengan mencari sumber di internet atau web lainnya.